2015
DOI: 10.1002/ana.24546
|View full text |Cite
|
Sign up to set email alerts
|

Tau positron emission tomographic imaging in aging and early Alzheimer disease

Abstract: Objective Detection of focal brain tau deposition during life could greatly facilitate accurate diagnosis of Alzheimer’s disease (AD), staging and monitoring of disease progression, and development of disease modifying therapies. Methods We acquired tau positron emission tomography (PET) using 18F T807 (AV1451), and amyloid-β PET using 11C Pittsburgh Compound B (PIB) in older clinically normal individuals, and symptomatic patients with mild cognitive impairment or mild AD dementia. Results We found abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

81
898
5
10

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 855 publications
(994 citation statements)
references
References 39 publications
81
898
5
10
Order By: Relevance
“…Tau PET can also be used for Braak staging of participants. Data suggest that most amyloid-positive patients with AD are in Braak stage VI, while the majority of amyloid-negative patients with AD had Braak stages of III or lower [41,44]. Across AD and CN participants, tau PET measures also significantly correlate with cerebrospinal fluid (CSF) levels of amyloid and tau [39].…”
Section: Tau Imaging Research Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tau PET can also be used for Braak staging of participants. Data suggest that most amyloid-positive patients with AD are in Braak stage VI, while the majority of amyloid-negative patients with AD had Braak stages of III or lower [41,44]. Across AD and CN participants, tau PET measures also significantly correlate with cerebrospinal fluid (CSF) levels of amyloid and tau [39].…”
Section: Tau Imaging Research Findingsmentioning
confidence: 99%
“…Specifically, patients with AD show significant tau PET tracer uptake in the temporal, parietal, and frontal lobes, while the primary sensory/motor cortices are relatively spared [30,[39][40][41][42][43][44]. Tau in the inferior temporal lobe is associated with increased amyloid deposition on PET, as well as greater cognitive impairment and disease severity in AD [41,44]. Tau PET can also be used for Braak staging of participants.…”
Section: Tau Imaging Research Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Human studies evaluating AV-1451 tracer retention in aging and Alzheimer disease (AD) have indicated that in vivo binding patterns parallel existing neuropathologic staging of tau. 4,5 Despite the applicability of this ligand for imaging tau in aging and dementia, in certain conditions tracer binding might complicate image interpretation. Pathologic studies have found AV-1451 also showing retention unrelated to tau; this off-target binding may reflect iron deposition, neuromelanin, or vascular factors.…”
mentioning
confidence: 99%
“…2,3 An outbreak of ZIKV infection in New Caledonia occurred in 2014 with 1,380 confirmed cases within a population of 263,000. 4 We report 2 cases of myasthenia gravis (MG) with prior ZIKV infection.…”
mentioning
confidence: 99%